Comparative performance evaluation of four photovoltaic technologies in saharan climates of Algeria: ghardaïa pilot station - Sid Ahmed Tadjer; Abdelhakim idir; Fathia Chekired (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The aim of this paper is to present an evaluation of the performancerate of four different photovoltaic techniques in the Saharan environment. The purpose of this study is to investigate, analyse, discuss and illustrate the most effective of the different photovoltaic cell technologies (monocrystalline , amorphous silicon , poly-crystalline silicon  and cadmium telluridethin film  ) installed in Ghardaia which is located in southern of Algeria’s Sahara desert. In order to choose the most suitable technology in the Saharan climate conditions, the energy values produced by the plant were compared to those found by the PVSYST sizing software. The results show that thin-film and amorphous silicon panels produce low illumination, so they are the best choice for the Saharan environment.